Community Pride Proposal - Joy Jordan (EDIS, 2003)
This document is 4HCSO10 of the Florida 4-H Youth Development Program, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Reviewed June 2002.